Epitaxially integrated hierarchical ZnO/Au/SrTiO3 and ZnO/Ag/Al2O3 heterostructures: Three-dimensional plasmo-photonic nanoarchitecturing - Yoo, Youngdong; Kim, Minjung; Kim, Bongsoo (Nanomaterials, 2021)
In this study, we fabricated three-dimensional (3D) hierarchical plasmo-photonic nanoarchitectures by epitaxially integrating semiconducting zinc oxide (ZnO) nanowires with vertically oriented plasmonic gold (Au) and silver (Ag) nanoplatforms and investigated their growth mechanisms in detail. We synthesized 3D hierarchical Au–ZnO nanostructures via a vapor–solid mechanism leading to the epitaxial growth of ZnO nanowires on vertically oriented single-crystalline Au nanowires on a strontium titanate (SrTiO3) substrate. The elongated half-octahedral Au nanowires with a rhombus cross-section were transformed into thermodynamically stable elongated cuboctahedral Au nanowires with a hexagonal cross-section during the reaction. After the transformation, ZnO thin films with six twinned domains were formed on the side planes of the elongated cuboctahedral Au nanowire trunks, and six ZnO nanowire branches were grown on the ZnO thin films. Further, 3D hierarchical Ag–ZnO nanostructures were obtained via the same vapor–solid mechanism leading to the epitaxial growth of ZnO nanowires on vertically oriented Ag nanoplates on an aluminum oxide (Al2O3) substrate. Therefore, the growth mechanism developed herein can be generally employed to fabricate 3D hierarchical plasmo-photonic nanoarchitectures.
Keywords: Epitaxial; Heterostructure; Hierarchical; Nanoarchitecturing; Plasmo-photonic; Three-dimensional